"Vad är det här? Vi jobbar ju med mjuka värden" - En kvalitativ studie av uppfattningar om HR analytics i praktiken - Andersson,Louise; Brobeck,Ellen (2024)
The purpose of the study is to analyze how HR analysts understand their prerequisites for using HR analytics in a way that is perceived as legitimate. Today, there are expectations on HR to become a function that uses digital tools to analyze personnel key figures. In parallel, however, prevailing expectations on maintaining legitimacy by working with relational issues supporting more soft values, create challenges when they start using such new technologies. In the study, five HR analysts were interviewed about their experiences of using such technologies. The interviews were analyzed by drawing on institutional theory as well as previous research in the field. The results indicated several advantages when using HR analytics according to the interviewees. Among other things, control increases, it contributes to cost efficiency and better communication between different departments in the organization. However, there are also several challenges, such as getting others to understand the meaning of HR analytics in order to use it in a valuable way, maintaining legitimacy, legislation, technical limitations and opposition. To further research HR analytics, the managers and other employees in both HR and other departments' point of view could be explored to gain a broader understanding. It would also be interesting to compare similarities and differences in the public and private sectors to see if it is a contributing factor to how HR analytics is perceived and used.
Keywords: HR analytics; digitalisering; legitimitet; strategisk partner; institutionell teori; evidensbaserade metoder; digitization; legitimacy; strategic partner; institutional theory; evidence-based methods